2005
DOI: 10.1074/jbc.m412145200
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Keratan Sulfate in the Aggrecan Interglobular Domain Potentiates Aggrecanase Activity

Abstract: Keratan sulfate is thought to influence the cleavage of aggrecan by metalloenzymes. We have therefore produced a recombinant substrate, substituted with keratan sulfate, suitable for the study of aggrecanolysis in vitro. Recombinant human G1-G2 was produced in primary bovine keratocytes using a vaccinia virus expression system. Following purification and digestion with specific hydrolases, fluorophore-assisted carbohydrate electrophoresis was used to confirm the presence of the monosulfated Gal-GlcNAc6S and Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 61 publications
(67 reference statements)
2
27
0
Order By: Relevance
“…In contrast, chondroitin 6-sulfate (the major GAG component of human aggrecan) (24) was able to enhance TIMP-3 potency to a level much more similar to that of aggrecan when added at equivalent concentrations of GAGs. Interestingly, keratan sulfate, which has been shown to potentiate aggrecanase activity and which is the predominant GAG found near the Glu 373 -Ala 374 cleavage site (25), had no effect at all on TIMP-3 interactions. These results therefore suggest that the enhanced potency observed with aggrecan is mediated primarily through GAG-binding interactions, potentially through the FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, chondroitin 6-sulfate (the major GAG component of human aggrecan) (24) was able to enhance TIMP-3 potency to a level much more similar to that of aggrecan when added at equivalent concentrations of GAGs. Interestingly, keratan sulfate, which has been shown to potentiate aggrecanase activity and which is the predominant GAG found near the Glu 373 -Ala 374 cleavage site (25), had no effect at all on TIMP-3 interactions. These results therefore suggest that the enhanced potency observed with aggrecan is mediated primarily through GAG-binding interactions, potentially through the FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should also be noted that, in this study, we investigated only a single form of keratan sulfate, which has been reported previously to undergo both age-related changes in chain length, sulfation, fucosylation, and sialic acid capping (26) and to vary in structure between the keratan sulfate-rich region and interglobular domain of aggrecan (25). Therefore, it remains a possibility that alternative forms of keratan sulfate may demonstrate properties different from those observed in this study.…”
Section: Table 4 Effects Of Adamts-4 C-terminal Domains On the Interamentioning
confidence: 99%
“…Experiments using rHuADAMTS-4 have suggested that lower molecular weight enzyme isoforms (55-30 kd) cleave at the IGD-aggrecanase site, while higher molecular weight isoforms cleave aggrecan within its C-terminal chondroitin sulfate attachment regions (13,15). The apparent absence of low molecular weight isoforms of ADAMTS-4 and ADAMTS-5 isolated from extracts of agarose plugs may result from masking of the epitopes through binding of the enzyme isoforms to aggrecan mediated through interaction with keratan sulfate (26). Following cleavage of the aggrecan substrate within the extracellular matrix and subsequent release of aggrecan catabolites to the culture media, dissociation of the low molecular weight ADAMTS-4 and ADAMTS-5 isoforms may occur.…”
Section: Discussionmentioning
confidence: 99%
“…The dialyzed extracts were applied to an HA-Sepharose column equilibrated in PBS, and the G1-NITEGE fragments were eluted with buffered 4M GuHCl as described previously for G1-G2 (19,31). Purified G1-ITEGE (1.776 mg) was digested with 100 g/ml trypsin-activated MMP-13 for 22 hours at 37°C to generate G1-DIPEN.…”
Section: Methodsmentioning
confidence: 99%